Incentive policies for transboundary marine spatial planning: an evolutionary game theory-based analysis. (15th June 2022) - Wang, Shuo; Liu, Chao; Hou, Yuting; Xue, Xiongzhi
Abstract: Marine spatial planning (MSP), which is a step-by-step approach for the ecosystem-based management (EBM) of global oceans, enables human activity and marine and coastal ecosystems conservation to occur simultaneously. It contributes to the implementation of the 2030 Agenda, particularly Sustainable Development Goal 14. However, the MSP, supposed as a transboundary policy-making process, is hampered by obstacles. Although existing studies have revealed significant obstacles and enablers for transboundary marine spatial planning (TMSP), they have not analyzed how these factors affect government decision-making. To fill this gap, this paper takes the Xiamen–Kinmen Sea area in China as an example and analyses the interaction between the Xiamen–Zhangzhou–Quanzhou (XZQ) governments, the Kinmen government, and an introduced transboundary institution using evolutionary game theory. Numerical simulation is used to analyse the impact of influencing factors on the behaviors of different actors. The results demonstrate that: (1) the initial probability of the three parties directly affect the final stability; (2) net benefits have a positive incentivizing effect on the performance of the Promotion Group; (3) the value of eco-environmental losses reflects the urgency of collaborative governance by implementing TMSP; (4) transaction costs do not undermine collaboration, but do reduce the willingness of governments to participate if they are too high; and (5) the appropriate value of the transaction cost allocation coefficient should not exceed 0.9. This research may serve as an essential reference for the Xiamen–Kinmen Sea area for implementing EBM and provide general insights into the design of incentive policy recommendations for other regions for developing TMSP in shared waters. Graphical abstract: Image 1 Highlights: A tripartite evolutionary game model to explore factors for TMSP is developed. The players' evolution routine and optimal result for TMSP are revealed. Initial possibilities affect the player's decision-making behavior. The choice of the transboundary institution relies on the benefits from TMSP. Transaction costs do not undermine the collaboration unless they are too high.